DOI: 10.14264/uql.2016.469
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the pharmacokinetics and pharmacodynamics of omeprazole in the horse

Abstract: Equine Gastric Ulcer Syndrome (EGUS) is a common condition of the horse, affecting a broad range of horse usages and types. Recently the terminology of the syndrome has been expanded to include terms Equine Squamous Gastric Disease (ESGD) and Equine Glandular Gastric Disease (EGGD) to describe diseases of the squamous and glandular mucosa of the stomach, respectively. Omeprazole, a proton pump inhibitor that blocks acid production, is considered the treatment of choice for EGUS and it has been widely used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(203 reference statements)
0
3
0
Order By: Relevance
“…Whilst there is a widely held view that once daily administration of ORLO results in 24 hours of acid suppression based on early studies (Jenkins et al., 1992 ; Daurio et al., 1999 ), the average duration of acid suppression with oral treatment at 4 mg/kg was under 12 hours in one study (Merritt et al., 2003 ) and may be much lower in horses on a high forage diet (Sykes, 2016 ). In many animals the duration of acid suppression with ORLO may not be sufficient for EGGD healing, particularly in the pyloric region where pH is lowest.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there is a widely held view that once daily administration of ORLO results in 24 hours of acid suppression based on early studies (Jenkins et al., 1992 ; Daurio et al., 1999 ), the average duration of acid suppression with oral treatment at 4 mg/kg was under 12 hours in one study (Merritt et al., 2003 ) and may be much lower in horses on a high forage diet (Sykes, 2016 ). In many animals the duration of acid suppression with ORLO may not be sufficient for EGGD healing, particularly in the pyloric region where pH is lowest.…”
Section: Discussionmentioning
confidence: 99%
“…When omeprazole is administered via an oral route, variation between horses may be compounded by differences in bioavailability which can vary up to 10‐fold (Sykes, Underwood, et al, ). Although initial reports indicated that oral omeprazole suppressed acid production for the 24‐hr period between doses (Daurio et al, ; Jenkins et al, ), more recent studies suggest that for at least half the 24‐hr treatment interval there may be insufficient acid suppression to promote healing of the squamous mucosa (Merritt, Sanchez, Burrow, Church, & Ludzia, ), particularly in horses that are fed a high forage diet (Sykes, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential weakness is that the presence of the PEG tube and gastropexy may have altered gastric motility. The use of PEG‐instrumented horses allowed for the concurrent measurement of intragastric pH as part of separate studies investigated the pharmacodynamics of omeprazole in the horse (Sykes et al ., ). A potential effect of the PEG tube and gastropexy via alterations in gastric motility and emptying on the pharmacokinetics reported in this study cannot be completely discounted.…”
Section: Discussionmentioning
confidence: 99%